The Antioxidant Alpha-Lipoic Acid Inhibits Proliferation and Invasion of Human Gastric Cancer Cells via Suppression of STAT3-Mediated MUC4 Gene Expression. (13th December 2019) - Yang, Yu; Fang, Erhu; Luo, Jiajun; Wu, Hongxue; Jiang, Yue; Liu, Ying; Tong, Shilun; Wang, Zhihua; Zhou, Rui; Tong, Qiang
Abstract : Background . Metastasis and invasion are the main causes of mortality in gastric cancer. To improve the treatment of gastric cancer, the development of effective and innovative antitumor agents toward invasion and proliferation is needed. Alpha-lipoic acid (ALA), a naturally occurring thiol antioxidant, showed antiproliferative and cytotoxic effects on several cancers. So it is feasible to explore whether ALA can be used to inhibit proliferation and invasion in human gastric cancer. Methods . The expression of MUC4 in human gastric cancer tissues was assayed by immunohistochemistry. Then, we performed in vitro cell proliferation and invasion analysis to explore the antitumor effect of ALA using AGS, BGC-823, and MKN-28 cells. To further explore the mechanism of ALA-mediated downregulation of MUC4, we cotransfected human gastric cancer cells with STAT3 siRNA and STAT3 overexpression construct. ChIP assays were carried out to find the relationship between MUC4 and STAT3. Results . We found that the MUC4 gene was strongly expressed in human gastric cancer tissues. Meanwhile, ALA reduced proliferation and invasion of human gastric cancer cells by suppressing MUC4 expression. We also found that STAT3 was involved in the inhibition of MUC4 by ALA. Mechanistically, ALA suppressed MUC4 expression by inhibiting STAT3 binding to the MUC4 promoter region. Conclusion . ALA inhibits both proliferation and invasion of gastric cancer cells by suppression of STAT3-mediated MUC4 gene expression.